Building a Child and Youth Care Culture of Relational-Centred Praxis: Ours to Make - Bellefeuille, Gerard; Stiller, Rebecca; Neuman, Stephen; Deol, Jack; Smith, Cole; Brown, Mackenzie; Gautreau, Holly; Diduch, Andrea (American Journal of Education and Learning, 2017)
Our purpose here is to draw upon the insights, perspectives, and ideas we have acquired in life and in our professional practice experiences as child and youth care (CYC) students, practitioners, and educators so we can frame a much needed discussion about the concept of praxis as considered from a relational ontological perspective. Our premise is that to truly fulfil the vision of being a relational-centred profession grounded in the core values and principles of trust, fairness, integrity, honesty, caring, tolerance, and respect for diversity and equality, CYC practitioners must reach deeper into the nuance of the concept of praxis to fully grasp its meaning from a relational-centred perspective. Thus, we present the case that a teaching and learning pedagogy that encourages critical thinking and promotes relational-centred praxis is more likely to bring about the deep learning and self-refection CYC practitioners must acquire to generate the inspiration, confidence, competence, and moral courage necessary to act as transformational leaders in the field.